The interactive knee (London : Primal, 1998)
A three-dimensional color graphic model of the knee, displayed and labeled in detail. Includes the anatomy, surgical procedures, biomechanics, and magnetic resonance image (MRI) of the human knee.
CD is available at Koleksi Media Perpustakaan HUKM
System requirements : Pentium processor; Windows 95/98, or Windows NT 4.0.
Keywords: Knee -- Radiography